THE INFLUENCE OF SOCIAL MEDIA AND ENTREPRENEURSHIP KNOWLEDGE ON INTEREST IN ENTREPRENEURSHIP THROUGH BUSINESS MOTIVATION OF STUDENTS OF THE FACULTY OF ECONOMICS AND BUSINESS HASANUDDIN UNIVERSITY MAKASSAR - Nirwana Nirwana; Muhammad Ismail; Abdul Razak Munir (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2021)
This study aims to determine the effect of social media and entrepreneurial knowledge on interest in entrepreneurship through business motivation in students of the Faculty of Economics and Business at Hasanuddin University. This research was conducted at the Faculty of Economics and Business at Hasanuuddin University by taking information from students in 2018 using a questionnaire, with a total sample of 200 students. The data were analyzed using a quantitative approach and processed using the SPSS version 22 application. The results of this study indicate that social media has a significant effect on business motivation for economic and business faculty students, in contrast to entrepreneurial knowledge which has no significant effect on economic and business faculty students. Then the influence of social media, entrepreneurial knowledge and business motivation have a positive effect on business interest in economics and business faculty students. Then based on the results of the intervening the influence of social media and business knowledge has a significant effect on business interest through business motivation. This shows that students of the Faculty of Economics and Business at the Indonesian Muslim University have a high enthusiasm for entrepreneurship.